A germline-limited piggyBac transposase gene is required for precise excision in Tetrahymena genome rearrangement. Issue 16 (26th July 2017) - Feng, Lifang; Wang, Guangying; Hamilton, Eileen P.; Xiong, Jie; Yan, Guanxiong; Chen, Kai; Chen, Xiao; Dui, Wen; Plemens, Amber; Khadr, Lara; Dhanekula, Arjune; Juma, Mina; et al.
Abstract: Developmentally programmed genome rearrangement accompanies differentiation of the silent germline micronucleus into the transcriptionally active somatic macronucleus in the ciliated protozoan Tetrahymena thermophila . Internal eliminated sequences (IES) are excised, followed by rejoining of MAC-destined sequences, while fragmentation occurs at conserved chromosome breakage sequences, generating macronuclear chromosomes. Some macronuclear chromosomes, referred to as non-maintained chromosomes (NMC), are lost soon after differentiation. Large NMC contain genes implicated in development-specific roles. One such gene encodes the domesticated piggyBac transposase TPB6, required for heterochromatin-dependent precise excision of IES residing within exons of functionally important genes. These conserved exonic IES determine alternative transcription products in the developing macronucleus; some even contain free-standing genes. Examples of precise loss of some exonic IES in the micronucleus and retention of others in the macronucleus of related species suggest an evolutionary analogy to introns. Our results reveal that germline-limited sequences can encode genes with specific expression patterns and development-related functions, which may be a recurring theme in eukaryotic organisms experiencing programmed genome rearrangement during germline to soma differentiation.